Endogenous entry/exit as an alternative explanation for the disciplining role of independent analysts - Lys, Thomas Z.; Sunder, Jayanthi (Journal of Accounting and Economics, 2008)
Gu and Xue [2008. The superiority and disciplining role of independent analysts. Journal of Accounting and Economics, this issue, doi:10.1016/j.jacceco.2008.02.002] study the disciplining effect of independent analysts on the accuracy and forecast relevance of the forecasts of non-independent analysts. One of the intriguing results is that while independent analysts issue inferior forecasts, their presence appears to reduce the forecast bias, improve the forecast accuracy and increase the forecast relevance of forecasts issued by non-independent analysts. We explore alternative explanations for the Gu–Xue results. Our evidence of endogenous entry and exit of independent analysts provides a more compelling explanation for the reported results.